Case Report: Can Inhaled Adenosine Attenuate COVID-19? - Spiess, Bruce D.; Sitkovsky, Michael; Correale, Pierpaolo; Gravenstein, Nikolaus; Garvan, Cynthia; Morey, Timothy E.; Fahy, Brenda G.; Hendeles, Leslie; Pliura, Thomas J.; Martin, Thomas D.; Wu, Velyn; Astrom, Corey; et al. (Frontiers in Pharmacology, 2021)
Coronavirus disease 2019 (COVID-19) has caused a pandemic of complex inflammatory syndromes heralded by acute respiratory distress syndrome (ARDS) and thrombotic complications. Standard thinking is that the coronavirus attacks cells through attachment to angiotensin-converting enzyme proteins. New work in pharmacology suggests that perhaps adenosine-regulator proteins may play a role in the pathogenesis’s of COVID-19 infection. Furthermore, adenosine, by interacting with cell receptor sites, has pluripotent effects upon inflammatory cells, is anti-inflammatory, and is important in tissue hypoxia signaling. Inhaled adenosine is safe. Thousands have received it for asthmatic challenge testing. It has recently been used in Italy by this route with remarkable efficacy in COVID-19. We describe the first two cases of adenosine use in the United States in patients with COVID-19 that we believe were otherwise going to die within hours. The effects of adenosine were rapid, positive, and fit the pharmacologic hypotheses made about how it might be a therapeutic exogenously administered nucleoside.